KRIPTOGRAFI HILL-CHIPER MENGGUNAKAN MODULAR GANJIL DAN GENAP - Albinur Limbong (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2018)
Due to the advancement of information and communication technology, securing data or information is one of the important task to do. Cryptography is one of a computational science that develop very fast in order to protect data or information. One of method used in cryptography is Hill chiper, i.e.a methode used to convert plaintext to become chipertext vice versa, by using a matrix. Hill chiper is one of cryptography algorithm using symmetrical keys. Hill chiper algorithm uses an invertible matrix n x n as a key to encrypt, to covert plaintext to become chipertext, or to decrypt, to convert chipertext back to plaintext. For encryption the plaintext, which is converted into number, is multiplied by the enchipering matrix, and the results, which in number, are again converted into texts. Due to the fact that it uses matrix as a key for encryption or decryption, then Hill chiper is very difficult to break. In some references, text to be converted has 26 alphabets and the matrix used to convert is also even modular. In fact, the length of the different texts to be converted is not limited to 26, it can be longer than 26, and the converting matrix can also be odd modular. This paper disscuss the Hill chiper cryptography by using a matrix not only even modular but also odd modular.